Influence of Competency and Soft Skill on Teachers' Performance through Teachers' Creativity - Serlin Serang; Roslina Alam; Aryati Arfah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine and analyze the effect of competence and soft skills on teacher performance through teacher creativity at MAN Malakaji Gowa. The research approach used a quantitative approach. The researcher used a saturated sampling technique sample, with a sample size of 60 teachers. Sources of data used in this study are primary data and secondary data. The data was obtained using a questionnaire distributed directly to the respondents. Analysis and processing of data in this study using descriptive analysis using SPSS. This research concluded that the results of the partial test of competence and soft skills had a positive and significant effect on teacher creativity. Competence and Soft Skills contribute to teachers' creativity by 60.40%. Partially competence, soft skills, and creativity of teachers positively and significantly affect teacher performance. The contribution of competence, soft skills, and teacher creativity to teacher creativity is 70.4%. In addition, teacher creativity also has a positive and significant effect on teacher performance. Furthermore, from the results of the indirect influence research, competence and soft skills have a positive and significant effect on teacher performance which is mediated by teacher creativity.